Assessing the Socio-Economic Impacts of Rural Infrastructure Projects on Community Development - Shahid Hussain; Rashid Maqbool; Ammar Hussain; Saleha Ashfaq (Buildings, 2022)
Public construction infrastructure projects have been recognized as one of the fundamental tools in enhancing community socio-economic conditions for community development. The purpose of this study is to empirically investigate the impacts of socio-economic factors on community development of rural regions. Through a questionnaire survey administrated in Pakistan, public construction practitioners’ views were sought and evaluated. Empirical support for the argument originated from the data collected from 213 respondents in Pakistan’s public construction industry. The questionnaire’s data were evaluated employing the partial least square structural equation modeling (PLS-SEM). The study’s findings showed that economic and social factors influence the community development of rural regions. The result obtained from PLS-SEM proposed a more viable method to realize community development and objectives. The study’s results have offered precious lessons for local authorities, policymakers, and project stakeholders to strengthen the drive for achieving community development goals. Strategies supporting community development in rural regions are indispensable for local community development. This study provides empirical confirmation for the understanding and combining the community development concept; it illuminates absent knowledge about community development, especially in rural regions. This is one of the few studies investigating the influencing dimensions of community development in rural regions. To the authors’ best knowledge, this is the first research article providing empirical evidence of the influencing dimensions of community development in rural regions in a developing country.